2003
DOI: 10.1577/1548-8675(2003)023<0431:mdvams>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Variation and Mixed-Stock Analysis of Recreational and Commercial Walleye Fisheries in Eastern Lake Erie

Abstract: The relative contributions of five spawning stocks of walleye Stizostedion vitreum to three recreational derbies and a commercial fishery operating in eastern Lake Erie in 1995 and 1996 were estimated by analyzing mitochondrial DNA (mtDNA) variation and by using a maximum likelihood model. Simulations of fishery mixtures (N ϭ 100) were used to assess the performance of the likelihood model for estimating contributions from three baselines composed of the five Lake Erie spawning stocks: Chickenolee Reef and Hur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…In randomly-mating diploid organisms, observed heterozygosity (H O ) from the microsatellite data and haplotype diversity (h) from the mitochondrial RFLP data are comparable as measures of genetic diversity (Nei and Tajima, 1981). Average H O for Lake Winnipeg was 0.66 and h was 0.52, values which are comparable to each other, as well as to values found in Cedar Lake (within the Lake Winnipeg drainage: H O = 0.587 by Stepien et al (2009)), and in the Laurentian Great Lakes: H O = 0.686-0.735 (Stepien et al, 2009) andh = 0.447-0.828 (McParland et al, 1999;Gatt and McParland, 2003). This indicates that genetic diversity within Lake Winnipeg is comparable to that found in other large lake walleye populations experiencing similar pressures (e.g., commercial fishing, invasive species and eutrophication), despite the somewhat longer evolutionary history of the Laurentian system.…”
Section: Genetic Diversity Within Lake Winnipeg Walleyesupporting
confidence: 71%
“…In randomly-mating diploid organisms, observed heterozygosity (H O ) from the microsatellite data and haplotype diversity (h) from the mitochondrial RFLP data are comparable as measures of genetic diversity (Nei and Tajima, 1981). Average H O for Lake Winnipeg was 0.66 and h was 0.52, values which are comparable to each other, as well as to values found in Cedar Lake (within the Lake Winnipeg drainage: H O = 0.587 by Stepien et al (2009)), and in the Laurentian Great Lakes: H O = 0.686-0.735 (Stepien et al, 2009) andh = 0.447-0.828 (McParland et al, 1999;Gatt and McParland, 2003). This indicates that genetic diversity within Lake Winnipeg is comparable to that found in other large lake walleye populations experiencing similar pressures (e.g., commercial fishing, invasive species and eutrophication), despite the somewhat longer evolutionary history of the Laurentian system.…”
Section: Genetic Diversity Within Lake Winnipeg Walleyesupporting
confidence: 71%
“…Molecular genetic markers and established methods of statistical inference have been widely used in fisheries management (Carvalho and Hauser 2004;Pella and Masuda 2004) and in other basic and applied sciences (Manel et al 2005). Specifically, mixed-stock analysis has been widely used to provide compositional estimates of harvests from population mixtures in both marine (e.g., Beacham and Wood 1999;Ruzzante et al 2000;Seeb et al 2004) and freshwater (e.g., Gatt et al 2003) realms as well as to quantify spatiotemporal variation in population contributions in habitats occupied during nonspawning periods (Potvin and Bernatchez 2001). While the majority of studies have focused on species of economic importance, increasing attention has been directed towards species of conservation concern (e.g., sturgeon; Waldman et al 1996).…”
mentioning
confidence: 99%
“…The interaction of bathymetry, temperature, and food abundance in the three basins in Lake Erie may cause variation in walleye abundance and spatial distribution. Lake Erie walleyes have been managed as a single stock, but are comprised of several genetically distinct stocks (Merker and Woodruff 1996;Stepien and Faber 1998;McParland et al 1999;Gatt et al 2003). Previous tagging studies suggested that walleye stocks in western Lake Erie migrate north to LSC and Lake Huron, while stocks in Lake Huron and LSC also migrate south to Lake Erie through connecting waters (Wolfert 1963;Ferguson and Derksen 1971;Haas et al 1988;Todd and Haas 1993).…”
mentioning
confidence: 99%